2022
DOI: 10.3389/fimmu.2022.927474
|View full text |Cite
|
Sign up to set email alerts
|

PSEN1 is associated with colon cancer development via potential influences on PD-L1 nuclear translocation and tumor-immune interactions

Abstract: Presenilin 1 (PSEN1), as a catalytical core of the γ-secretase complex, plays multiple actions through mediating transmembrane domain shedding of the substrates. Unlike extensive studies performed on investigating the functions of γ-secretase substrates or the effects of γ-secretase inhibitors, our findings uncover a potential action of PSEN1 on PD-L1 alternative truncation and nuclear translocation, broadening our understanding on how the γ-secretase contributes to colon cancer development as well as suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Presenilin-1 (PSEN1) and presenilin-2 (PSEN2) are two genes associated with several diseases, and early studies have focused on their association with familial Alzheimer's disease (FAD), which often leads to early onset of the disease 36 38 . Many recent studies had proved that PNEN1 was involved in the initiation and development of tumors and was always accompanied by bad effects 39 , 40 . KEGG showed that PNEN1, as an upstream protein, positively regulated the process of β- catenin protein entering the nucleus, which promoted the occurrence of tumors 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Presenilin-1 (PSEN1) and presenilin-2 (PSEN2) are two genes associated with several diseases, and early studies have focused on their association with familial Alzheimer's disease (FAD), which often leads to early onset of the disease 36 38 . Many recent studies had proved that PNEN1 was involved in the initiation and development of tumors and was always accompanied by bad effects 39 , 40 . KEGG showed that PNEN1, as an upstream protein, positively regulated the process of β- catenin protein entering the nucleus, which promoted the occurrence of tumors 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%